The Optimization of Capital Structure in Maximizing Profit and Corporate Value - Kharisya Ayu Effendi (Binus Business Review, 2017)
The purpose of this research was to determine the optimal capital structure which could maximize profits and corporate value. The used method was quantitative descriptive analysis. Moreover, the data used was secondarydata in the Jakarta Islamic Index (JII) from 2011 to 2015. The results of this research show that companies which have optimal capital structure are in line with the trade-off theory models. The capital structure is optimal if thedebt levels are to a certain extent so that the corporate value will increase. However, if the debt limit passes the certain degree, profit and corporate value will decrease. Meanwhile, pecking order theory in this research doesnot conform and cannot be said to be optimal because of the low debt level describing the opposite result with the theory as low profits.